ILAI ETIKA DALAM KALÃŽLAH WA DIMNAH KARYA IBN AL-MUQAFFAâ€™ - Puriyadi, Puriyadi (Jurnal Ilmiah Ilmu Ushuluddin, 2010)
The study of ethics as a philosophical subject has been rare in Islamic tradi-tion compared to other subjects. It is in this context that a study of ethicscontained in Ibn al-Muqaffa?s Kalîlah wa Dimnah is very important. ForIbn al-Muqaffa?, the position of ethics is higher than religion itself. Thus,one should do a good thing, even though religion does not command it. Heargues that to live a life in accordance with moral values will lead a personto happiness and dignity. It is significant that he uses fables to communi-cate his ethical ideas. Through fables, he can persuade people to use not onlyreason, but also emotion and imagination, to understand ethics.